Hubungan Self Esteem dengan Kecenderungan Perilaku Self Injury pada Siswa SMA serta Implikasi dalam Layanan Bimbingan Konseling - Triyanti, Tessa; Neviyarni, Neviyarni (Universitas Negeri Padang, 2025)
Abstract Self-injury is often used by adolescents as a way to cope with emotional distress, yet cases in schools frequently remain hidden and unaddressed systematically. This study aims to examine the relationship between self-esteem and the tendency to engage in self-injury among students of SMA TAMANSISWA in the 2024/2025 academic year, along with its implications for school counseling services. This correlational quantitative research involved 57 students selected through total sampling. Self-esteem was measured using a culturally and linguistically adapted version of the Rosenberg Self-Esteem Scale (RSES) for high school students at TAMANSISWA, employing the original scoring system. The tendency for self-injury was assessed using a cultural adapted version of the Klonsky’s Inventory of Statements About Self-Injury (ISAS), with items adapted to reflect commonly observed behaviors in the school environment and scored according to standardized intensity frequency indicators. Content validity was evaluated through expert judgment, and internal reliability met the criteria for acceptability. Data were analyzed using descriptive statistics and Spearman’s rank correlation test. The majority of students fell into the moderate category for both self-esteem (84.21%) and self-injury tendency (64.91%). The analysis revealed a significant negative correlation of moderate strength (r = -0.452; p < 0.000), indicating that higher self-esteem is associated with lower self-injury tendencies. These findings highlight the urgency for counseling programs focused on enhancing self-esteem, promoting adaptive emotional regulation, fostering peer support, and implementing early interventions. Abstrak Self-Injury kerap digunakan remaja untuk meredakan distres emosional, namun kasus di sekolah sering tersembunyi dan belum tertangani secara sistematis. Penelitian ini bertujuan mengetahui Hubungan self-esteem dengan kecenderungan self-injury pada siswa SMA TAMANSISWA Tahun Ajaran 2024/2025 serta Implikasinya bagi layanan bimbingan konseling (BK). Penelitian Kuantitatif korelasional ini melibatkan 57 siswa (total sampling). Self Esteem diukur menggunakan Rosenberg Self-Esteem Scale (RSES) yang di adaptasi agar sesuai konteks budaya dan bahasa remaja SMA di TAMANSISWA, dengan sistem penskoran asli. Kecenderungan self-injury diukur menggunakan skala Inventory of Statements About Self-Injury (ISAS) Klonsky, di mana butir disesuaikan dengan konteks budaya. Validitas isi dikaji melalui judgment dan reliabilitas internal memenuhi kriteria kelayakan. Data dianalisis menggunakan statistik deskriptif dan uji koreasi Spearman. Mayoritas siswa berada pada kategori self-esteem sedang (84,21%) dan self-injury sedang (64,91%). Hasil analisis menunjukkan korelasi negatif signifikan berkekuatan sedang (p = -0,452; p < 0,000), mengindikasikan bahwa peningkatan self-esteem berasosiasi dengan penurunan kecenderungan self-injury. Hasil menegaskan pentingnya program BK yang berfokus pada penguatan harga diri, pelatihan regulasi emosi adaptif, dukungan sebaya dan intervensi dini.